2013
DOI: 10.1186/1742-4755-10-59
|View full text |Cite
|
Sign up to set email alerts
|

Unintended pregnancy: magnitude and correlates in six urban sites in Senegal

Abstract: BackgroundIn Senegal, unintended pregnancy has become a growing concern in public health circles. It has often been described through the press as a sensational subject with emphasis on the multiple infanticide cases as a main consequence, especially among young unmarried girls. Less scientific evidence is known on this topic, as fertility issues are rarely discussed within couples. In a context where urbanization is strong, economic insecurity is persistent and the population is globalizing, it is important t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 19 publications
4
18
1
Order By: Relevance
“…The relationship between education and pregnancy intention has been inconsistent from previous studies (Mutumbi, 2013;Palamuleni & Adebowale, 2014;Ikamari et al, 2013;Habte, Teklu, Melese, & Magafu, 2013;Izugbara, 2014;Geda & Lako, 2011;Faye et al, 2013;Goto, Yasumura, Reich, & Fukao, 2002;Geelheod, Nayembil, Asare, van Leeuwen, & van Roomalen, 2002;Kassa, Berhane, & Worku, 2012). However, our study showed that the level of education was a significant determinant of pregnancy intention.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…The relationship between education and pregnancy intention has been inconsistent from previous studies (Mutumbi, 2013;Palamuleni & Adebowale, 2014;Ikamari et al, 2013;Habte, Teklu, Melese, & Magafu, 2013;Izugbara, 2014;Geda & Lako, 2011;Faye et al, 2013;Goto, Yasumura, Reich, & Fukao, 2002;Geelheod, Nayembil, Asare, van Leeuwen, & van Roomalen, 2002;Kassa, Berhane, & Worku, 2012). However, our study showed that the level of education was a significant determinant of pregnancy intention.…”
Section: Discussioncontrasting
confidence: 98%
“…The prevalence of unintended pregnancy varies from place to place depending on people's sexual behaviour and contraceptive acceptance and use. In sub-Saharan Africa, unintended pregnancy accounted for about 39% of the 49 million pregnancies that occurred in 2008 (Faye et al, 2013). In Nigeria about one in three women of reproductive age had experienced an unplanned pregnancy (Sudhinaraset, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In this study unplanned pregnancy was 29.9% among the study participants. This findings is in agreements with the findings from other studies in Ethiopia [36] and Kenya [18] but it is lower than the other studies that were conducted in Jimma 35% [37] and Hosana 34% [19], this might be due to the increased availability and accessibility of maternal health services, including access to modern family planning with time. More over this finding were much lower than the findings of studies conducted in Tanzania 45.9% [38] and Nepal 41.1% [35].…”
Section: Discussionsupporting
confidence: 91%
“…These findings echo high levels of unintended pregnancies found in urban Senegal, higher among poorer women36, and indicate that there are still substantial barriers to contraceptive use that need to be addressed. The stagnation in unmet need observed among harder-to-reach women does not necessarily indicate a lack of progress in these groups: in a context of rising percent demand satisfied, this lack of change rather reflects parallel increases in MCPR and in the total demand for FP (defined as the sum of contraceptive use and unmet need).…”
Section: Discussionmentioning
confidence: 55%